The Association Between Human Leukocyte Antigens and ITP, TTP, and HIT. Issue 2 (March 2019) - Amin Asnafi, Ali; Jalali, Mohammad Taha; Pezeshki, Seyed Mohammad Sadegh; Jaseb, Kaveh; Saki, Najmaldin
Abstract : Background: Autoimmune thrombocytopenia in immune thrombocytopenic purpura (ITP), thrombotic thrombocytopenic purpura (TTP), and heparin-induced thrombocytopenia (HIT) is associated with immunologic degradation of platelets and reduced platelet counts in patients, leading to bleeding risk in patients. Considering the role of human leukocyte antigens (HLA) in the development of immune response, in this review, we examine the relationship between HLA and pathogenesis of the above-mentioned diseases. Methods: Relevant English-language literature was searched and retrieved from Google Scholar search engine and PubMed database (1979 to 2018). The following keywords were used: "Immune Thrombocytopenic purpura, " "Thrombotic Thrombocytopenic Purpura, " Human Leukocyte Antigen, " and "Heparin-induced thrombocytopenia." Results: In autoimmune thrombocytopenia, HLA molecule presents self-antigens or foreign antigens similar to self-antigens, provoking an immune response against platelets that results in the degradation of platelets in peripheral blood and possible bleeding in the patient. For example, HLA-DRB1 *11 presents the self-antigen and induces an immune response against ADAMTS13, which is associated with thrombocytopenia in TTP patients. Conclusions: HLA alleles can be used as prognostic biomarkers for immunologic disorders of platelet such as ITP, TTP, and HIT. Different DRB1 alleles enable the assessment of resistance to common ITP treatments as well as disease prognosis. Due to the genetic association between HLA-DR1 and HLA-DQ1 alleles and the role of HLA-DRB1 *11 in TTP, the HLA-DQB1 *02: 02 allele may also play a role in TTP pathogenesis.